Behavior of Elastic Therapeutic Tapes under Dynamic and Static Conditions - Hermela Ejegu; Bipin Kumar; Priyanka Gupta (Advances in Materials Science and Engineering)
The aim of this paper is to determine the relaxation behavior of the therapeutic tape under different thermomechanical conditions over different time spans and to analyze the physical and mechanical properties of selected kinesiology tapes. The relaxation test was conducted under a static condition with two extended levels (25% and 50%) for one hour and a dynamic condition for 300 cycles with different loading-unloading values, strain rates, and temperatures. For both static and dynamic conditions, at a lower strain rate and higher load and temperature, the therapeutic tapes showed higher loss of internal stress and faster losses of efficiency. Under all selected conditions, the tape’s stress has decreased rapidly.